SCREENING OF PHYTOCHEMICALS AND IN VITRO ANTIDIABETIC ACTIVITY OF BAUHINIA RACEMOSA LAM. LEAVES - Gawade, Bhimraj; Farooqui, Mazahar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In this study, the leaves of medicinal plant Bauhinia racemosa Lam. with different pharmacological activities were subjected to phytochemical screening and assessment of their in vitro inhibitory potential with porcine pancreatic α-amylase enzyme to treat and management of diabetes. Methods: Plant leaves were extracted sequentially with ethanol solvent. A modified 3,5-dinitrosalicylic acid method was adopted to screen α-amylase inhibition assay. The ethanol extract was analyzed qualitatively and gas chromatography–mass spectrometry analysis technique for the active phytoconstituents according to the standard protocols. Results: A phytochemical screening of leaves extract reveals the presence of carbohydrate, alkaloids, saponin, glycosides, steroids, tannins, flavonoids, triterpenoid, and phenolic compounds. The ethanol extract reported inhibition of α-amylase enzyme activity at IC50 value 61.72 ± 0.03 μg/mL and acarbose as a standard drug at IC50 value 28.07 ± 0.02 μg/mL. Conclusion: The results of the study indicate that B. racemosa Lam. leaves contain some of bioactive phytochemicals might to be exhibiting in vitro antidiabetic activity, which was leading to decreases the rate of starch digestion.